Synthesis and studies of anticancer and antimicrobial activity ofnew phenylurenyl chalcone derivatives - ÖZTÜRK, MEHMET (My University, 2022)
© 2022 Bentham Science Publishers.Background: Phenylurenyl chalcone structures have the potential to act as a scaffold in anticancer drug discovery. Methods: N-Phenethyl-N\"-{4-[(2E)-3-phenylprop-2-enoyl]phenyl}urea, 4/3-[(2E)-3-substitutedphenylprop-2-enoyl]phenyl}-N-phenylurea,4/3-[(2E)-3-substitutedphenyl. prop-2-enoyl]phenyl}-N-methylphenyl urea and {4/3-[(2E)-3-substitutedphenylprop-2-enoyl]phenyl}-N-ethylphenyl urea derivatives(1-35) were prepared and evaluated for their anticancer and antimicrobial activity against A-549 Hep-3B, HT-29, CF-7, PC-3, K-562 NIH-3T3 and Huh-7 cell lines and against Staphylococcus aureus (ATCC 6538), Pseudomonas aeruginosa (ATCC 9027), Escherichia coli (ATCC 8739) and Candida albicans (ATCC 10231), respectively. Results: While compounds 2, 26, 29, and 34 showed moderate cytotoxic activity on cell line Huh 7, compounds 14 (IC50: 6.42 µM), 16 (IC50: 5.64 µM), 19 (IC50: 6.95 µM) and 34 (IC50: 6.87 µM) showed good cytotoxic activity on Huh-7 cell line close to Sorafenib (IC50: 4.29 µM) (as reference). MIC values of compounds 4 and 22 against E. coli were 25 μg/ml, compounds 3, 14 and 29 against P. aeruginosa 25 μg/ml, and compounds 11 and 33 against S. aureus 25 μg/ml. On the other hand, the minimum inhibitory concentration of all tested compounds against C. albicans was 25 μg/ml. Conclusion: N-Phenethyl-N\"-{4-[(2E)-3-phenylprop-2-enoyl]phenyl}urea may be a new candidate to be developed as an anticancer compound.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TROPİKAL TIP; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; TROPICAL MEDICINE; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmasötik bilim; İlaç Keşfi; Molecular Medicine; Pharmaceutical Science; Drug Discovery; Urea; phenylurenyl chalcone; kinase inhibitors; anticancer; antimicrobial; cytotoxicity; TYROSINE KINASE INHIBITORS; UREA DERIVATIVES; ANTIBACTERIAL ACTIVITY; BIOLOGICAL EVALUATION; MOLECULAR DOCKING; DESIGN; CYTOTOXICITY; PREDICTION